Narrowing the FOXF1 distant enhancer region on 16q24.1 critical for ACDMPV. Issue 1 (December 2016) - Szafranski, Przemyslaw; Herrera, Carmen; Proe, Lori; Coffman, Brittany; Kearney, Debra; Popek, Edwina; Stankiewicz, Paweł
Abstract Background Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a rare lethal lung developmental disorder caused by heterozygous point mutations or genomic deletions involvingFOXF1 or its 60-kb tissue-specific enhancer region mapping 270 kb upstream ofFOXF1 and involving fetal lung-expressed long non-coding RNA genes and CpG-enriched sites. Recently, we have proposed that theFOXF1 locus at 16q24.1 may be a subject of genomic imprinting. Findings Using custom-designed aCGH and Sanger sequencing, we have identified a novel de novo 104 kb genomic deletion upstream ofFOXF1 in a patient with histopathologically verified full phenotype of ACDMPV. This deletion allowed us to further narrow theFOXF1 enhancer region and identify its critical 15-kb core interval, essential for lung development. This interval harbors binding sites for lung-expressed transcription factors, including GATA3, ESR1, and YY1, and is flanked by the lncRNA genes and CpG islands. Bisulfite sequencing of one of these CpG islands on the non-deleted allele showed that it is predominantly methylated on the maternal chromosome 16. Conclusions Substantial narrowing and bisulfite sequencing of theFOXF1 enhancer region on 16q24.1 provided new insights into its regulatory function and genomic imprinting.